Albert Watkins and Howard Watkins Family Genealogy Trip to Tennessee - Watkins, Howard::::::::: (1986)
Frances Beasley Fine and Albert Watkins in front of John Ross Home Home in Rossville, Georgia (just south of Chattanooga)